2014
DOI: 10.3109/10253890.2014.910650
|View full text |Cite
|
Sign up to set email alerts
|

Social defeat stress induces a depression-like phenotype in adolescent male c57BL/6 mice

Abstract: Exposure to stress is highly correlated with the emergence of mood-related illnesses. Because major depressive disorder often emerges in adolescence, we assessed the effects of social defeat stress on responses to depressive-like behaviors in juvenile mice. To do this, postnatal day (PD) 35 male c57BL/6 mice were exposed to 10 days of social defeat stress (PD35–44), while control mice were handled daily. Twenty-four hours after the last episode of defeat (PD45), separate groups of mice were tested in the socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
140
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 234 publications
(164 citation statements)
references
References 53 publications
15
140
2
3
Order By: Relevance
“…In particular, sexual and reproductive behaviors were severely suppressed in subordinate male rats [1,5,22,[80][81][82][83][84][85][86]. Studies from other laboratories indicated similar aversive effects of social stress on physiological processes and social behaviors in mice [87][88][89][90]. As in rats, subordinate male mice were found to emit fewer ultrasonic vocalizations and exhibited reduced sexual behaviors as compared to dominant male mice [91][92][93][94].…”
Section: Discussionmentioning
confidence: 95%
“…In particular, sexual and reproductive behaviors were severely suppressed in subordinate male rats [1,5,22,[80][81][82][83][84][85][86]. Studies from other laboratories indicated similar aversive effects of social stress on physiological processes and social behaviors in mice [87][88][89][90]. As in rats, subordinate male mice were found to emit fewer ultrasonic vocalizations and exhibited reduced sexual behaviors as compared to dominant male mice [91][92][93][94].…”
Section: Discussionmentioning
confidence: 95%
“…Van Kampen et al 2000) and mice (e.g. Iñiguez et al 2014). In contrast, other studies have reported no significant decrease in activity (Monleón et al 2015(Monleón et al , 2016 or hyperactivity (Venzala et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Watt et al 2009, Toth andNeumann 2013) and depression (e.g. Venzala, et al 2012, Iñiguez et al 2014, in order to determine the underlying mechanisms and identify potential pharmacological treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has characterized chronic stress as one of the primary causal factors for the development and persistence of depressive behavioral phenotypes (Iniguez et al, 2014; Kleiman et al, 2014; Mahar et al, 2014; Monroe et al, 2014; Morris et al, 2014; Nederhof et al, 2014; Saravanan and Wilks, 2014; Shapero et al, 2014; Sickmann et al, 2014; Vinkers et al, 2014). In addition, exposure to stressful life events synergistically interacts with residual depressive symptoms (i.e., high depression scores following therapeutic interventions), to increase the risk of relapsing to a depressed state (Harkness et al, 2014).…”
Section: The Role Of Stress In Depressionmentioning
confidence: 99%